Synthesis of Emindole SB - George, David T.; Kuenstner, Eric J.; Pronin, Sergey V. (Synlett, 2017)
Paxilline indole diterpenes have been a subject of scientific inquiry for over 30 years due to their diverse biological activities and unique structural features. These efforts resulted in a multitude of synthetic approaches and a dozen completed synthesis. Here, we discuss our contributions to this area that culminated in an 11-step synthesis of (±)-emindole SB.
Keywords: natural products; synthesis; terpenoids; indoles; polycyclization; radical addition; stereoselectivity